Dynamic behaviors of angular contact ball bearing with a localized surface defect considering the influence of cage and oil lubrication. (August 2021) - Wen, Chengwei; Meng, Xianghui; Fang, Congcong; Gu, Jiaming; Xiao, Lin; Jiang, Shuang
Highlights: A complete multi-DOF dynamic model for defective cases is established. The effects of outer raceway defect on bearing dynamic behaviors are revealed. The traction in ball-raceway contact changes rapidly around defect exit event. The defect greatly affects load characteristics and angular misalignments. Reciprocating collisions between ball and pocket will result from surface defect. Abstract: Angular contact ball bearing plays a significant role in guaranteeing the service performance of the mechanical equipment. However, the occurrence of localized defect dramatically affects the tribo-dynamic performance of the bearing, which can further result in serious accidents. Considering the influence of cage and oil lubrication, this paper proposes a complete multi-degree-of-freedom (DOF) dynamic model for defective angular contact ball bearing by analyzing the full multi-body interactions. The defect is modeled in the geometrical constraint relationships to replace the excitation functions proposed in previous studies. Based on the analysis of high-speed conditions, the effects of outer raceway defects with different sizes and position angles on the dynamic behaviors of the bearing are revealed. It is found that the defect significantly influences the load characteristics and the angular misalignments, and the traction in the ball-raceway contact shows an abrupt change around the defect exit event. The results also show that the reciprocating collisions between the ball and the cage pocket occur in the defective case which are affected by the defect scale and the bearing speed.